CHENGQI, TONGZILIAO AND YINTANG POINT ACUPUNCTURE IN IMPROVING THE CASE OF MYOPIA VISUS - Wulandari, Mayang; Mahadini, Chantika (Journal of Vocational Health Studies, 2018)
Background: Myopia, commonly referred to as shortsightedness, is one of the top five causes of blindness worldwide. It is said that in patients with myopia, intraocular pressure has a relationship that tends to increase at the severity of myopia. Purpose: To analyze the effect of acupuncture in improving myopia visus. Method: The method used in this research was pre-experimental design with the pretest-posttest design. Experimental research is an experimental activity, which aims to find out a symptom or influence that arises, as a result of certain treatments. Result: Acupuncture could improve myopia vision. Conclusion: Acupuncture could repair myopia vision and provided some opportunities for sustainable scientific development through subsequent research on myopia.